Investigating the Effectiveness of Videos Designed Using Cognitive Load Theory on Biology Students’ Academic Achievement - Azman, A. N.; Johari, M. (Jurnal Pendidikan IPA Indonesia, 2022)
This study seeks to investigate the effect of videos designed based on cognitive load theory on students’ academic performance. A one-group pre-test-post-test design was employed, with 25 lower sixth Biology students from one of the sixth form centres in Brunei as participants of the study, conveniently selected (non-random sampling). Twelve cycles of lessons on 12 different biology topics were conducted; for each cycle, a pretest was administered before students watched the videos (self-learning), followed by a posttest after the videos were watched. This study found a significant increase in test scores after students watched the videos for all of the cycles, with a large effect size ranging from .76 to .93 according to Cohen’s interpretation. The study shows how the cognitive load theory can help instructional designers create better learning content to encourage student learning. It can therefore be concluded that carefully curated videos are able to help reduce students’ extrinsic load. Thus, this finding has implications for the importance of theory-based video creation in helping students’ learning that most technologically innovative pedagogies seem to leverage on. One recommendation for future study worth delving into would be to directly measure students’ comparative cognitive load to investigate how their cognitive load changes before and after watching videos.